Hubungan Antara Kebutuhan Afiliasi Dengan Fear of Missing Out (FoMO) Pada Mahasiswa Pengguna Media Sosial Instagram - Triyono, Triyono; Isnaini, Lutfi Ayu (ANFUSINA: Journal of Psychology, 2021)
The purpose of this study was to determine the relationship between the need for affiliation with Fear of Missing Out on students using Instagram social media. This research is a correlational quantitative research. The population in this study were students of the Faculty of Ushuluddin and Da'wah UIN Raden Mas Said Surakarta totaling 3981 students. The number of samples was 364 students who were selected through cluster random sampling.  The data collection uses affiliation needs scale and Fear of Missing Out scale. The results of the study used product moment correlation analysis which showed that Ha was accepted and Ho was rejected. So it can be concluded that there is a positive relationship between the need for affiliation with Fear of Missing Out with a correlation coefficient of 0.453 with a significant level of 0.000 (p <0.05). That is, the higher the level of need for affiliation, the higher the level of Fear of Missing Out in students and vice versa.